2019
DOI: 10.7759/cureus.5223
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Prenatal Exposures in Children with and Without a Diagnosis of Autism Spectrum Disorder

Abstract: The current study was a case-control, focused on the presence of environmental exposures during pregnancy in mothers of children diagnosed with autism spectrum disorder (ASD) and children who were not. Exposures investigated included: acetaminophen/paracetamol use, air pollution, fever, smoking, parental age, maternal diabetes, prenatal vitamin use, workplace exposures, recreational drug use, seafood consumption, obesity, and maternal thyroid issues. Two-hundred and fifteen mothers of children (107 with ASD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 15 publications
(15 reference statements)
0
32
0
Order By: Relevance
“…Our null findings for maternal smoking are similar to results from many other studies and meta‐analyses (Bilder et al, 2009; Burstyn et al, 2010; Caramaschi et al, 2018; Dodds et al, 2011; Jung et al, 2017; Lee et al, 2012; Lei et al, 2015; Maimburg & Væth, 2006; Mandic‐Maravic et al, 2019; Nilsen et al, 2013; Wang et al, 2017), but this is the first study to confirm this by use of a tobacco biomarker. Of the prior studies reporting positive findings (Duan et al, 2014; Hultman et al, 2002; Jiang et al, 2016; Mrozek‐Budzyn et al, 2013; Nilsen et al, 2013; Saunders et al, 2019; Tran et al, 2013), only one other study controlled for SES (Tran et al, 2013). Smoking is differential across SES (Hiscock et al, 2012) and thus a relationship between smoking and ASD in these studies may be an indicator of a relationship between SES and ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our null findings for maternal smoking are similar to results from many other studies and meta‐analyses (Bilder et al, 2009; Burstyn et al, 2010; Caramaschi et al, 2018; Dodds et al, 2011; Jung et al, 2017; Lee et al, 2012; Lei et al, 2015; Maimburg & Væth, 2006; Mandic‐Maravic et al, 2019; Nilsen et al, 2013; Wang et al, 2017), but this is the first study to confirm this by use of a tobacco biomarker. Of the prior studies reporting positive findings (Duan et al, 2014; Hultman et al, 2002; Jiang et al, 2016; Mrozek‐Budzyn et al, 2013; Nilsen et al, 2013; Saunders et al, 2019; Tran et al, 2013), only one other study controlled for SES (Tran et al, 2013). Smoking is differential across SES (Hiscock et al, 2012) and thus a relationship between smoking and ASD in these studies may be an indicator of a relationship between SES and ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta‐analyses on smoking and ASD (Jung et al, 2017; Wang et al, 2017), examining 22 and 9 studies respectively, found null results overall associated with self‐reported smoking, as did several individual studies (Bilder et al, 2009; Burstyn et al, 2010; Caramaschi et al, 2018; Dodds et al, 2011; Lee et al, 2012; Lei et al, 2015; Maimburg & Væth, 2006; Mandic‐Maravic et al, 2019; Nilsen et al, 2013). Positive associations were found in a few national registries (Hultman et al, 2002; Nilsen et al, 2013; Tran et al, 2013) and smaller case–control studies (Duan et al, 2014; Jiang et al, 2016; Mrozek‐Budzyn et al, 2013; Saunders et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With an estimated prevalence of 1 in 59 children in the United States [Baio et al, 2018], ASD has a growing public health importance. Evidence supports the prenatal origins of ASD [Courchesne et al, 2019], with both genetic and environmental factors known to play a role [Saunders, Woodland, & Gander, 2019]. Maternal diet is known to impact fetal development; established examples include the associations between folic acid and neural tube defects and nutrient deprivation and schizophrenia [McGrath, Brown, & St Clair, 2010;McNulty et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal diet is known to impact fetal development; established examples include the associations between folic acid and neural tube defects and nutrient deprivation and schizophrenia [McGrath, Brown, & St Clair, 2010;McNulty et al, 2019]. Emerging evidence has linked certain maternal dietary factors with ASD as well, including reports of protective associations between prenatal vitamin supplements/folic acid, and vitamin D and ASD [B. K. Lee et al, 2019;McNulty et al, 2019;Saunders et al, 2019]. However, other critical nutrients may also influence risk of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that more than half of ASD cases are attributable to environmental factors. The use of medications, cigarettes, later gestational age at the start of prenatal vitamins have all been correlated with ASD diagnosis [4]. Consequently, the search for additional environmental factors is very reasonable, but what about the potential mechanisms between exposure to acetaminophen and the development of ASD?…”
mentioning
confidence: 99%